Effect of Gliricidia sepium and Macaranga peltata leaves on seed germination and seedling growth of Cow pea - Hima Karthikeyan , Sarathy; Elsa Mathew, Aleena; Jo, Aleena (Indian Journal of Agroforestry, 2025)
Gliricidia sepium (Jacq.) Kunth and Macaranga peltata (Roxb.) Mull. Arg. are two multipurpose trees commonly cultivated as a component of agroforestry system in tropics. The allelopathic effect of leaf leachates of these trees on germination and growth of three selected varieties of cowpea (Vigna unguiculata L. Walp.) were examined. The germination studies were conducted using two different concentrations of leaf leachates, in triplicates. Data regarding seed germination, shoot length and root length were collected. The experimental data obtained was statistically analysed using ANOVA and LSD at 5% level of significance. The results showed that seed germination was significantly affected by G. sepium leaf leachates. Among the seedling growth parameters, shoot length and root length were significantly inhibited by G. sepium leaf leachates whereas stimulatory effect was observed for M. peltate leaf leachates. Considering the inhibitory effect of G. sepium on cowpea, it is further recommended that farmers should be cautious while including the plant as a part of agroforestry system. M. peltata can be chosen as a suitable agroforestry component for cowpea cultivation, after further field studies.